Adverse drug reaction suggests by a clinical vignette - Finestone AJ (Clinical Interventions in Aging, 2011)
Albert J FinestoneTemple University School of Medicine, Philadelphia, PA, USAI had a three-lobe pneumonia and toxic encephalopathy in 2004. A lumbar puncture did not show meningitis. Magnetic resonance imaging showed a macroadenoma of the pituitary gland. Prolactin level was significantly elevated, making the diagnosis a functioning prolactinoma requiring treatment. Initially, I was treated with the dopamineagonist cabergoline, which is also used in much larger doses to treat Parkinsonism. Recent reports have indicated heart valve damage in Parkinsonism patients treated with ergot-derived dopamine-receptor agonists.